Pain, Emotion and Cognition A Complex Nexus - Pickering, Gisèle; Gibson, Stephen; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book focuses on the reciprocal interactions between pain, emotion and cognition. International experts report on their findings, clinical experience and the most recent literature on the complex relations between these three domains. Clinical, psychological, behavioral and neuroimaging approaches converge towards aiding patients suffering from pain, cognitive impairment or emotional distress. Beyond the pathophysiological aspects of pain, difficulties encountered with patients are analyzed and strategies are proposed to optimize treatment, doctor-patient relationships, and patient well-being. This work will appeal to a broad readership, from clinical medical practitioners to psychologists, nurses and pain specialists.
Part I Nociception, Pain, Emotion and Cognition Interconnections -- Cognitive Psychology and Neuropsychology of Nociception and Pain -- Emotional Aspects of Chronic Pain -- Cerebral and Spinal Modulation of Pain by Emotions and Attention -- Understanding the Suffering of Others: The Sources and Consequences of Third-person Pain -- Neuroplasticity in the Pain, Emotion and Cognition Nexus -- Part II Measurement Issues -- Tools that Should be Considered in Pain Assessment: Cognitive Factors, Emotion and Personality -- Pain Evaluation in Patients with Cognitive Impairment -- Behavioural/Facial Markers of Pain, Emotion, Cognition -- Part III Management Issues -- Pharmacological Pain Management: For Better or for Worse? -- Psychological Approaches to the Management of Pain, Cognition and Emotion -- Physical Therapy and Exercise: Impacts on Pain, Mood, Cognition, and Function -- Part IV Special Populations -- Phantom Pain: The Role of Maladaptive Plasticity, Emotional and Cognitive Variables -- Pain in Parkinson Patients -- Clinical Pain in Schizophrenia, a Forgotten Area -- The Pain, Emotion and Cognition Nexus in Older Persons and in Dementia.
Keywords: Pain medicine; Neurology .; Psychiatry; Radiology; Pain Medicine; Neurology; Psychiatry; Imaging / Radiology